Detail in contemporary hotel design - Plunkett, Drew; Reid, Olga (London : Laurence King Publishing, 2013)
Hotel interiors need to satisfy the imaginations of their customers and whet the appetite for a return visit or recommendation, and the design that gets the formula right will do as much to prolong the life of the business as the service delivered within the hotel. This book explores in detail 48 of the best recent hotel interior design schemes, featuring projects by leading architects from around the world. The book is divided into three sections embracing newly built and refurbished hotels as well as conversions. Each project includes photographs as well as detailed drawings and plans, where appropriate, as well as informative text describing the design concept and process.
boek